Assessing the impact of FOXP1 mutations on developmental verbal dyspraxia - Vernes, S; MacDermot, K; Monaco, A; Fisher, S (Macmillan Publishers Ltd., 2009)
Neurodevelopmental disorders that disturb speech and language are highly heritable. Isolation of the underlying genetic risk factors has been hampered by complexity of the phenotype and potentially large number of contributing genes. One exception is the identification of rare heterozygous mutations of the FOXP2 gene in a monogenic syndrome characterised by impaired sequencing of articulatory gestures, disrupting speech (developmental verbal dyspraxia, DVD), as well as multiple deficits in expressive and receptive language. The protein encoded by FOXP2 belongs to a divergent subgroup of forkhead-box transcription factors, with a distinctive DNA-binding domain and motifs that mediate hetero- and homodimerisation. FOXP1, the most closely related member of this subgroup, can directly interact with FOXP2 and is co-expressed in neural structures relevant to speech and language disorders. Moreover, investigations of songbird orthologues indicate that combinatorial actions of the two proteins may play important roles in vocal learning, leading to the suggestion that human FOXP1 should be considered a strong candidate for involvement in DVD. Thus, in this study, we screened the entire coding region of FOXP1 (exons and flanking intronic sequence) for nucleotide changes in a panel of probands used earlier to detect novel mutations in FOXP2. A non-synonymous coding change was identified in a single proband, yielding a proline-to-alanine change (P215A). However, this was also found in a random control sample. Analyses of non-coding SNP changes did not find any correlation with affection status. We conclude that FOXP1 mutations are unlikely to represent a major cause of DVD.